2021
DOI: 10.1177/0271678x20982395
|View full text |Cite
|
Sign up to set email alerts
|

Normative distribution of posterior circulation tissue time-to-maximum: Effects of anatomic variation, tracer kinetics, and implications for patient selection in posterior circulation ischemic stroke

Abstract: The generalization of perfusion-based, anterior circulation large vessel occlusion selection criteria to posterior circulation stroke is not straightforward due to physiologic delay, which we posit produces physiologic prolongation of the posterior circulation perfusion time-to-maximum (Tmax). To assess normative Tmax distributions, patients undergoing CTA/CTP for suspected ischemic stroke between 1/2018-3/2019 were retrospectively identified. Subjects with any cerebrovascular stenoses, or with follow-up MRI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…These results may indicate that autogenerated mismatch in CTP-RAPID cannot be used in pc-stroke due to inaccurate estimation, especially for ischemic cores. Consequently, Tmax, as used in the present study, might be a reasonable independent CTP-RAPID parameter for estimating penumbral volumes, despite the overestimation 16 17. The results may also explain the high cut-off value of Tmax >6 s in our results, considering the relatively small volume of posterior circulation compared with that of anterior circulation.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…These results may indicate that autogenerated mismatch in CTP-RAPID cannot be used in pc-stroke due to inaccurate estimation, especially for ischemic cores. Consequently, Tmax, as used in the present study, might be a reasonable independent CTP-RAPID parameter for estimating penumbral volumes, despite the overestimation 16 17. The results may also explain the high cut-off value of Tmax >6 s in our results, considering the relatively small volume of posterior circulation compared with that of anterior circulation.…”
Section: Discussionsupporting
confidence: 46%
“…CTP imaging criteria based on the tissue window benefited more patients with large vessel stroke due to the salvage of reversible tissue after reperfusion therapy. Unfortunately, to date, threshold-based perfusion selection criteria have not been applied in pc-stroke due to hemodynamic delay, anatomical imbalance and variation 16. Capasso et al 17 recently compared the diagnostic accuracy between qualitative and automatic evaluations of CTP parameters in pc-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 A recent study suggested that tissue at risk might be overestimated in the posterior circulation, most likely due to anatomical variations. 32 In BASICS, pc-ASPECTS did not influence functional outcome, whereas in BASILAR, a pc-ASPECTS score ⩾5 identified patients with a potential benefit of TE. 33…”
Section: Discussionmentioning
confidence: 93%
“…30,31 A recent study suggested that tissue at risk might be overestimated in the posterior circulation, most likely due to anatomical variations. 32 In BASICS, pc-ASPECTS did not influence functional outcome, whereas in BASILAR, a pc-ASPECTS score ⩾5 identified patients with a potential benefit of TE. International Journal of Stroke, 17 (9) In this study, functional outcome of patients with ACLVO was worse compared to previously published RCTs in ACLVO (mRS 0-2: HERMES: 46.0%, this study: 39.9%).…”
Section: Discussionmentioning
confidence: 93%
“…For example, Garcia-Esperon et al (4) reported a sensitivity of about 25% of lacunar strokes in the VB system to be recognized by multi-modal perfusion CT. Cerebellar infarction may be larger, but a good ability of multi-model perfusion CT to detect cerebellar infarction was found only for infarcts > 4-5 ml (5,6). Small structure size, the availability and the duration of the examination (MRI), the poor spatial resolution (CT), physiological variability of cerebral perfusion in this area (7), and the technical difficulties to measure cerebral blood flow correctly in this anatomical region hinder the application of the stroke mismatch concept to a broad range of VBS.…”
Section: Introductionmentioning
confidence: 99%